In situ and operando electron microscopy in heterogeneous catalysis—insights into multi-scale chemical dynamics. (26th February 2021) - Chee, See Wee; Lunkenbein, Thomas; Schlögl, Robert; Cuenya, Beatriz Roldan
Abstract: This review features state-of-the-art in situ and operando electron microscopy (EM) studies of heterogeneous catalysts in gas and liquid environments during reaction. Heterogeneous catalysts are important materials for the efficient production of chemicals/fuels on an industrial scale and for energy conversion applications. They also play a central role in various emerging technologies that are needed to ensure a sustainable future for our society. Currently, the rational design of catalysts has largely been hampered by our lack of insight into the working structures that exist during reaction and their associated properties. However, elucidating the working state of catalysts is not trivial, because catalysts are metastable functional materials that adapt dynamically to a specific reaction condition. The structural or morphological alterations induced by chemical reactions can also vary locally. A complete description of their morphologies requires that the microscopic studies undertaken span several length scales. EMs, especially transmission electron microscopes, are powerful tools for studying the structure of catalysts at the nanoscale because of their high spatial resolution, relatively high temporal resolution, and complementary capabilities for chemical analysis. Furthermore, recent advances have enabled the direct observation of catalysts under realistic environmental conditions using specialized reaction cells. Here, we will critically discuss the importance of spatially-resolved operando measurements and the available experimental setups that enable (1) correlated studies where EM observations are complemented by separate measurements of reaction kinetics or spectroscopic analysis of chemical species during reaction or (2) real-time studies where the dynamics of catalysts are followed with EM and the catalytic performance is extracted directly from the reaction cell that is within the EM column or chamber. Examples of current research in this field will be presented. Challenges in the experimental application of these techniques and our perspectives on the field's future directions will also be discussed.